Impact of COVID-19 convalescence on pregnancy outcomes in patients undergoing IVF/ICSI during fresh ART cycles: a retrospective cohort study - Cao, Mingya; Han, Yan; Feng, Tengfei; Lu, Peiyang; Wang, Yue; Sun, Qingyun; Zhao, Zhiming; Pan, Wensen (Frontiers in Endocrinology, 2024)
Objective: To study the impact of COVID-19 convalescence on female fertility and laboratory and clinical outcomes in fresh ART cycles.In this retrospective cohort study, we analyzed 294 patients who had recovered from COVID-19 and underwent fresh ART cycles between January and March 2023 (COVID-19 group). 631 patients in the same period in 2022 but without COVID-19 were non-COVID-19 group . comparing the basic characteristics and laboratory parameters of patients in both groups. The primary outcome measure was the clinical pregnancy rates. The FSH levels were significantly lower, and the AFC markedly higher in the COVID-19 group compared to the non-COVID-19 group (P<0.001 and P=0.004, respectively). The predominant ovarian stimulation protocol in the COVID-19 group was GnRH antagonist (64.85%, P<0.001), with a reduced Gn dosage and duration in comparison to the non-COVID-19 group (P<0.05). Although the number of blastocyst formations was lower in the COVID-19 group (P=0.017), this group exhibited a higher blastocyst freezing rate and a greater rate of high-quality embryos per retrieved oocyte (P<0.001 and P=0.023, respectively). Binary logistic regression analysis indicated that COVID-19 convalescence did not significantly impact clinical pregnancy rates in fresh transfer cycles (OR]= 1.16, 95CI= 0.68-1.96, P=0.5874). However, smooth curve fitting and threshold effect analysis revealed an age-related decline in clinical pregnancy rates in both groups, more pronounced in the COVID-19 group for women aged over 38 years with the likelihood of clinical pregnancy decreased by 53% with each additional year of age (OR = 0.81, 95% CI= 0.61-1.08, P=0.1460; OR = 0.47; 95% CI= 0.21,1.05, P=0.0647).Our findings indicate no substantial evidence of adverse effects on clinical pregnancy outcomes in patients undergoing in vitro fertilization (IVF) or intracytoplasmic sperm injection (ICSI) during the convalescence period of COVID-19 in fresh ART cycles. However, age emerges as a significant factor influencing these outcomes. Notably, for women above 38 years of age, the likelihood of clinical pregnancy in patients with a prior COVID-19 infection decreased by 53% with each additional year. This highlights the importance of considering maternal age, especially in the context of COVID-19, when evaluating the likelihood of successful pregnancy in ART treatments.